Suicide - Motta, Robert W.; Motta, Robert W. (IntechOpen, 2021)
The occurrence of suicide often startles those who knew the involved individual. The public often cannot believe that the person who committed suicide could have engaged in such a seemingly irrational and extreme act. Similarly, health agencies often find themselves at a loss as to what strategies or policies might be employed to stem the seemingly constant flow of suicide. This book carefully addresses sociological, psychological, and physiological factors that contribute to suicide. It also presents strategies that might be employed to reduce suicide by way of public policies, psychotherapeutic strategies, and neurophysiological interventions.
English
Keywords: Sociology; depression, risk factors, anxiety, happiness, concussion, self-regulation